A CROSS-SECTIONAL STUDY ON SOCIAL MEDIA ADDICTION AND ITS RELATIONSHIP WITH STRESS AND LONELINESS - MOHAMED BADAWI, MOHAMED ABD ELWAHAB; BINTI AMINUDIN, NUR SYAFIQAH; BIN NODRIN, MUHAMMAD HARITH IHSANUDDIN; GUNASEGARAN, GOPINATH; BINTI MOHD RIDZUAN, NUR BALQIS; ALABED, ALABED ALI A.; MOHAMMED A. ABDALQADER (Malaysian Journal of Public Health Medicine, 2024)
Over the previous few years, the allure of social media has surged, captivating an incredible number of people worldwide. People interact with each other not only face-to-face but also through social media platforms such as Facebook, Instagram, Tiktok and Twitter. Misuse or overuse of these platforms might have led to addiction especially in the younger generation. Social media addiction has emerged as a problem of global concern and researchers all around the world have been trying to find its relation with other possible consequences. This study aims to determine the prevalence of social media addiction, stress and loneliness among university students in Selangor. Additionally, we aim to study the association between sociodemographic factors, stress, loneliness and social media addiction. The study utilized a cross sectional research design and employed a convenience sampling method with a sample of 350 university students who are Malaysian, 18 years old and above as well as currently studying in universities around Selangor. Data collection was carried out through an online validated questionnaire which includes Personal Identification and Sociodemographic, Social Media Disorder Scale (SMD Scale), Perceived Stress Scale (PSS-10) and De Jong Gierveld Loneliness Scale. Results showed that 73.71% of students in Selangor had a prevalence of social media addiction and most were having moderate stress (82.4%) and feeling moderately lonely (73.4%). A significant association was found for social media addiction and stress but not with loneliness. Thus, by identifying the factors associated with social media addiction and its detrimental effects through this study, we aim to encourage development of targeted interventions and support mechanisms to alleviate its adverse effects.